2020
DOI: 10.1111/anu.13194
|View full text |Cite
|
Sign up to set email alerts
|

Dietary licorice ( Glycyrrhiza glabra ) improves growth, lipid metabolism, antioxidant and immune responses, and resistance to crowding stress in common carp, Cyprinus carpio

Abstract: Common carp (Cyprinus carpio) is widely reared in the polyculture system in Iran. In recent years, this species has reared in concrete ponds under high culture densities. Various aquaculture practices such as high stocking densities and crowding conditions can stimulate stress responses in cultured fish (Adineh et al., 2019; Xie et al., 2008). The stress response can elevate reactive oxygen species (ROS) and cause oxidative stress, immunosuppression and susceptibility to infectious diseases (Naderi et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…The main benefit of using herbs materials/extracts as natural sources of antioxidants is enhancing the growth and health status of aquatic organisms via improving the physiological functions and modulating the innate immune system (Adineh et al, 2021; Daniels & Hoseinifar, 2014; Gholamhosseini et al, 2020; Ngo et al, 2020; Yousefi et al, 2021). In the present study, Indian shrimp fed on diets supplemented with BO performed better in terms of growth and feed utilization than the control group and the optimum growth was observed in at levels of 2.5–5.0 g BO/kg diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main benefit of using herbs materials/extracts as natural sources of antioxidants is enhancing the growth and health status of aquatic organisms via improving the physiological functions and modulating the innate immune system (Adineh et al, 2021; Daniels & Hoseinifar, 2014; Gholamhosseini et al, 2020; Ngo et al, 2020; Yousefi et al, 2021). In the present study, Indian shrimp fed on diets supplemented with BO performed better in terms of growth and feed utilization than the control group and the optimum growth was observed in at levels of 2.5–5.0 g BO/kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers tend to increase the density of cultured animals in ponds to increase their production per unite area. This intensification may deteriorate the water quality leading to environmental stress, which could decrease the immunological response and induce opportunistic pathogens affecting the survival rate of aquatic animals (Adineh et al, 2021; Fazelan et al, 2020; Rajabiesterabadi et al, 2020; Yousefi et al, 2021). These bad conditions may also lead to outbreaks of disease causing massive mortality of cultured shrimp (Bondad‐Reantaso et al, 2012; Tinh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The complement system is the acute‐phase proteins of the immune system that play an active role in initiating inflammatory, chemotactic and phagocytic responses (Sunyer et al, 2005; Xie et al, 2006). The level of serum complement activity depends to a large extent on the health and efficiency of the liver (Adineh et al, 2021; Jia et al, 2019). Therefore, this improvement may be due to the properties of hepatoprotective and the reduction in oxidative stress by the Pro and Res, which has previously been suggested by Gabriel et al, 2015; Kuebutornye et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dügenci et al (2003) found no difference in growth performance of rainbow trout after feeding with mistletoe, nettle and ginger aqueous extracts. However, increased growth performance was observed in rainbow trout after treated with Viscum album (Yousefi,et al, 2021) and in carp after fed with Glycyrrhiza glabra (Adineh et al, 2021) and Cistus laurifolius (Bilen, Ali, et al 2021).…”
Section: Discussionmentioning
confidence: 99%